MANAGEMENT CONTROL IN THE PROCESS OF IMPLEMENTATION OF INNOVATION PROJECTS - POPOV, Alexander (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The scientific publication is dedicated to highlighting the systemic vision of the basics of management controlling in the process of implementing innovative projects and revealing the features of this type of controlling. It has been established that controlling the process of implementation of innovative projects is a special type of controlling, associated with their individuality and the absence of analogs and established patterns of analysis and control, and with the uncertainty of the final results of the project, its individual stages. It is substantiated that the control process is a process of step-by-step correction of expected project results, gradual control of parameters as the final result is approached. The procedure for determining the coefficient of change in the speed of work, which characterizes the execution of the network or operational-calendar schedule at the time of control, is considered. It is proposed to determine the relationship between the informational importance of control points and the implementation coefficient based on the value of the financial "penalty" function. The matrix of information weights of control points is considered, which is the basis for determining the sequence of polling points (objects) of control. The procedure for determining the step (control lag) for two interconnected innovative projects during the technological rehabilitation of production is revealed. The distribution function or the probability of the absence of uncertainty in the process of implementing works on the implementation of an innovative technological project before the moment of control is determined. Options for choosing the frequency of control point polls for operational management are substantiated. It was established that from the point of view of the stability of the information system, the algorithm for determining the maximum frequency of checks on the status of project implementation work should take into account the possibility of falling behind the given schedules and reducing the amount of remaining work, which results in an increase in the number of control point surveys. The limit of the increase is the time required for the implementation of decisions on operational regulation of the speed of work execution by production divisions (executors).
Keywords: controlling; project; innovations; technological project; information support; production